Analisis Wacana “Sinicization of Islam” Pemerintah China Terhadap Muslim Uyghur: Kritik Barat dan Pandangan Islam - Salma Regina; Ali Maksum (Mahesa Research Center, 2026)
This study aims to examine the discourse on policies implemented by Xi Jinping regarding the concept of “Sinicization of Islam” as well as Western criticism and Islamic perspectives. In recent years, the Chinese government under Xi Jinping has issued various policies to integrate religious practices with socialist values and Chinese culture. This has raised concerns about human rights violations and religious freedom for the Uyghur Muslim community. The type of research used is qualitative, while the data processing method used is descriptive discourse analysis by examining relevant documents. Data was obtained through secondary data collection techniques, including literature analysis and media reports. This study found that the discourse of Sinicization of Islam promoted by the Chinese government has been criticized by Western countries and is contrary to the principle of religious freedom in the Islamic perspective. The conclusion of this study emphasizes that the Sinicization policy can be understood as a form of cultural and political domination that causes tension between state ideology and universal values of humanity and Islam.